Determining fracture energy parameters of concrete from the modified compact tension test - A. Fernández-Canteli; L. Castañón; B. Nieto; M. Lozano; T. Holušová; S. Seitl (Fracture and Structural Integrity)
The modified compact tension (MCT) test, though not yet recognized as a valid test for determining fracture energy of concrete, is believed to represent a plausible and suitable alternative versus other well established procedures, such as the wedge-splitting test (WST) and the three point (3PB) or four point bending (4PB) tests, due to its simplicity and low cost. The aim of the paper is twofold: Firstly, to demonstrate the necessary correspondence between the experimental MCT test setup and finite element simulations and secondly, to initiate the way of establishing the desirable conversion between the fracture energy parameter values resulting from the MCT test and the standard conventional procedures. MCT tests are carried out and compared with the numerical results from 2-D and 3-D finite element calculations using the commercial codes ABAQUS and ATENA, the latter being specifically developed for applications on concrete structures and elements. In this way, the usability of the modified compact tension test for practical purposes is confirmed.